Infecção experimental de carrapatos (Amblyomma cajennense) em ratos com lepra Stefansky - H. C. de Souza-Araújo (Memorias do Instituto Oswaldo Cruz, 1943)
The A. succeeded, after various experiments, to infect ticks (Amblyoma cajennense) with STEFANSKY bacillus, upon feeding them in rats suffering from murine leprosy, in advanced stages. The A. thinks that will be ease to transfer the sickness from rat to rat by means of inoculation of triturate of infected ticks, as did MARCHOUX with Laelaps echdninus.